2003
DOI: 10.1289/ehp.5787
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and pathogenesis of uterine leiomyomas: a review.

Abstract: Uterine leiomyomas, or fibroids, represent a major public health problem. It is believed that these tumors develop in the majority of American women and become symptomatic in one-third of these women. They are the most frequent indication for hysterectomy in the United States. Although the initiator or initiators of fibroids are unknown, several predisposing factors have been identified, including age (late reproductive years), African-American ethnicity, nulliparity, and obesity. Nonrandom cytogenetic abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
400
4
16

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(432 citation statements)
references
References 280 publications
(353 reference statements)
12
400
4
16
Order By: Relevance
“…1 Aetiologies of uterine leiomyomas are unknown but several predisposing factors have been identified including age (late reproductive years), African-American ethnicity, nulliparity, obesity and genetics. 2 It is seven times commoner in blacks compared to Caucasians 3 and can grow so large to cause negative impact on obstetric outcome if co-existing with pregnancy. Estrogen is recognized as promoter of tumour growth.…”
Section: Introductionmentioning
confidence: 99%
“…1 Aetiologies of uterine leiomyomas are unknown but several predisposing factors have been identified including age (late reproductive years), African-American ethnicity, nulliparity, obesity and genetics. 2 It is seven times commoner in blacks compared to Caucasians 3 and can grow so large to cause negative impact on obstetric outcome if co-existing with pregnancy. Estrogen is recognized as promoter of tumour growth.…”
Section: Introductionmentioning
confidence: 99%
“…The factors related to tumorigenesis of leiomyomata can be categorized as risk factors, initiators, promoters, and effectors. 1 The causes of leiomyomata (initiators) remain unknown. Most identified leiomyomata-associated factors, such as local growth factors, ER, PR and nonrandom chromosomal alterations were considered to be promoters or effectors.…”
mentioning
confidence: 99%
“…Most identified leiomyomata-associated factors, such as local growth factors, ER, PR and nonrandom chromosomal alterations were considered to be promoters or effectors. 1 Some growth factors have been shown to be overexpressed in leiomyomata, and are hormonally regulated both in vivo and in vitro. These factors are either autocrine or paracrine, which promote mitogenic and fibrogenic action in these tissues.…”
mentioning
confidence: 99%
“…First, although the endometrial lining is not shed, the porcine estrous cycle occurs approximately every 21 days, and lasts for about 2-3 days, the duration of which more closely approximates menses observed in women compared to the rodent estrous cycle (Yuan and Carlson, 1987;The Merck Veterinary Manual, 8th ed., 1998;Swindle, 1998;Andersen et al, 2002b). This cyclicity of hormonal influences seems to play an important role in the development of uterine fibroids in women (Cramer et al, 1995;Andersen et al, 2002a;Flake et al, 2003), making the potbellied pig an appropriate model in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that hormonal influences play a significant role, due in part to continuous menstrual cycling (Flake et al, 2003). Molecular studies have identified differences in hormone receptor expression and further support a hormonemediated mechanism (Flake et al, 2003). Unfortunately, the lack of a suitable animal model has made it difficult to further elucidate the pathogenesis of fibroid formation, including the role of xenoestrogens in uterine leiomyoma development.…”
Section: Introductionmentioning
confidence: 99%